2007
DOI: 10.1093/humrep/dem315
|View full text |Cite
|
Sign up to set email alerts
|

Implantation is apparently unaffected by the dopamine agonist Cabergoline when administered to prevent ovarian hyperstimulation syndrome in women undergoing assisted reproduction treatment: a pilot study

Abstract: Administration of Cb2 in order to prevent OHSS is safe and does not appear to affect ART outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(50 citation statements)
references
References 45 publications
2
47
0
1
Order By: Relevance
“…However it was explored and found that women at risk for OHSS who had received this drug had fertilization, implantation and pregnancy rates comparable to those of controls, matched with respect to age, number and quality of the embryos replaced, embryonic stage at transfer and sperm quality. 29 Ongoing and full-term pregnancies were also similar in each group, and no major perinatal problems were detected. Cb2 administration in early pregnancy has not revealed to be harmful either, as published studies have reported employing it up to 7 mg per week, and the frequency of spontaneous and induced abortions and major congenital malformations were comparable with rates in the general population.…”
Section: Safety Profilementioning
confidence: 70%
See 1 more Smart Citation
“…However it was explored and found that women at risk for OHSS who had received this drug had fertilization, implantation and pregnancy rates comparable to those of controls, matched with respect to age, number and quality of the embryos replaced, embryonic stage at transfer and sperm quality. 29 Ongoing and full-term pregnancies were also similar in each group, and no major perinatal problems were detected. Cb2 administration in early pregnancy has not revealed to be harmful either, as published studies have reported employing it up to 7 mg per week, and the frequency of spontaneous and induced abortions and major congenital malformations were comparable with rates in the general population.…”
Section: Safety Profilementioning
confidence: 70%
“…38,39 However Alvarez et al in their study have presented that endometrial angiogenesis was not greatly altered, by the dose of Cb2 employed since neither implantation nor the overall ART outcome was affected. 29 …”
mentioning
confidence: 99%
“…dosage or type of medications [9,10], administration of intravenous albumin [11,12], dopamine agonists [13,14] and avoidance of ET, and thus pregnancy, immediately after stimulation with freezing of embryos for subsequent use [12,[15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, cabergoline reduces the occurrence of moderate-severe OHSS with no relevant negative effects on the number of retrieved oocytes or implantation rates and clinical pregnancy, without deleterious impact on pregnancy outcome 47,48 . Moreover, evaluating the long-term eff ects of prophylactic treatment with cabergoline, no negative impact on live birth rates and miscarriage rates without increased rate of congenital malformations of the babies born has been observed 49,50 . Quinagolide used in a fi xed regimen of three oral doses (50, 100 and 200 μg/day), starting on the day of hCG and continued for 17-21 days, signifi cantly reduces the frequency of moderate/severe early OHSS (12% vs. 13% vs. 4%) as compared with placebo (23%), without compromising pregnancy or treatment outcome.…”
Section: Dopamine Agonistsmentioning
confidence: 99%